2022
DOI: 10.1002/ptr.7673
|View full text |Cite
|
Sign up to set email alerts
|

Integrated gut microbiota and serum metabolomics reveal the protective effect of oleanolic acid on liver and kidney‐injured rats induced by Euphorbia pekinensis

Abstract: Euphorbia pekinensis (EP) is a commonly used Chinese medicine treating edema with potential hepatorenal toxicity. However, its toxic mechanism and prevention are remained to be explored. Oleanolic acid (OA) is a triterpene acid with potential hepatorenal protective activities. We investigated the protective effect and potential mechanism of OA on EP‐induced hepatorenal toxicity. In this study, rats were given total diterpenes from EP (TDEP, 16 mg/kg) combined with OA (10, 20, 40 mg/kg) by gavage for 4 weeks. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…As a result, many 16S rRNA gene sequence analyses considered the Phylum Verrucomicrobia to be a representative of Genus Akkermansia ( Cani et al, 2022 ). It has been demonstrated that there is a correlation between a reduction in the abundance of the Genus Akkermansia , a promising probiotic, and the development of various illnesses, including type 2 diabetes and inflammatory bowel disease ( Wang K. et al, 2022 ). In addition, the level of Genus Akkermansia was negatively correlated with the level of IR ( Shin et al, 2014 ; Watanabe et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, many 16S rRNA gene sequence analyses considered the Phylum Verrucomicrobia to be a representative of Genus Akkermansia ( Cani et al, 2022 ). It has been demonstrated that there is a correlation between a reduction in the abundance of the Genus Akkermansia , a promising probiotic, and the development of various illnesses, including type 2 diabetes and inflammatory bowel disease ( Wang K. et al, 2022 ). In addition, the level of Genus Akkermansia was negatively correlated with the level of IR ( Shin et al, 2014 ; Watanabe et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, most of the genera with significant differences were found to be significantly reduced in the model group, including Acetatifactor, Tuzzerella, Prevotellaceae , and [Eubacterium]_brachy_group . Acetatifactor is a strictly anaerobic Gram-positive bacterial genus from the Lachnospiraceae family, which is closely related to bile acid metabolic ( 28 ) and short-chain fatty acid metabolism ( 29 ). It has also been reported that Acetatifactor undergoes significant changes in colitis, and the regulation of acetylation factors plays a crucial role in relieving colitis ( 30 ).…”
Section: Discussionmentioning
confidence: 99%